2012
DOI: 10.1017/s1041610212000348
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the financial abuse of people with dementia: a qualitative study of safeguarding experiences in England

Abstract: Healthcare professionals may need to be more alert to the signs and risks of financial abuse in patients with dementia both at early and later stages. Engaging with safeguarding practitioners may facilitate prevention of abuse and effective response to those with substantial assets, but the monitoring of people with dementia needs to be sustained. In addition, professionals need to be alert to new risks from electronic crime. Researchers should consider including financial abuse in studies of elder abuse and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Whilst such involvement acknowledges that good familial and social networks certainly shape the perception of what is best for incapable patients (Keywood, 2003) -and therefore who better to help make these judgements than the older person's family members and close friends? -cautionary lessons from practice suggest that an over-reliance on relatives to safeguard the rights of incapacitated adults can sometimes lead to an erosion of the rights of incapable people and occasionally to their financial and physical abuse (Selwood and Cooper, 2009;Boyle, 2011;Bopp and Coleson, 1996;Keywood, 2003;Manthorpe, Samsi and Rapaport, 2012 (Redley, Clare, Luke and Holland, 2009) These concerns are echoed by Keywood, who identifies the difficulties relatives face accessing health and social care services when they are untrained or unsupported in that role (Keywood, 2003). Our own observations, albeit from a limited study carried out in a specific setting, suggest that family and close friends also struggle to deal with the emotional burdens associated with discharge planning (Stoller and Pugliesi, 1988) and lack timely information to make well-informed decisions about placement choices for patients at crucial planning meetings (Redley, Clare, Luke and Holland, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst such involvement acknowledges that good familial and social networks certainly shape the perception of what is best for incapable patients (Keywood, 2003) -and therefore who better to help make these judgements than the older person's family members and close friends? -cautionary lessons from practice suggest that an over-reliance on relatives to safeguard the rights of incapacitated adults can sometimes lead to an erosion of the rights of incapable people and occasionally to their financial and physical abuse (Selwood and Cooper, 2009;Boyle, 2011;Bopp and Coleson, 1996;Keywood, 2003;Manthorpe, Samsi and Rapaport, 2012 (Redley, Clare, Luke and Holland, 2009) These concerns are echoed by Keywood, who identifies the difficulties relatives face accessing health and social care services when they are untrained or unsupported in that role (Keywood, 2003). Our own observations, albeit from a limited study carried out in a specific setting, suggest that family and close friends also struggle to deal with the emotional burdens associated with discharge planning (Stoller and Pugliesi, 1988) and lack timely information to make well-informed decisions about placement choices for patients at crucial planning meetings (Redley, Clare, Luke and Holland, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…270 One exception to this was that many participants at time 2 were aware of the importance of financial planning and that they could promote understanding of this among their clients or service users. [265][266][267] This confidence was obvious about end-of-life care planning, except among care home managers who described undertaking such discussion with residents on moving into the home, but largely without reference to the MCA.…”
Section: Interpretation Of the Study Findings In Light Of Previous Rementioning
confidence: 99%
“…While research has shown that practitioners have some ability to identify abuse in extreme cases, they are less able to do so in more ambiguous situations [6]. They have been found to be not sufficiently alert to the warning signs of financial abuse [7]. Practitioners themselves have reported that they feel they lack the knowledge to detect elder abuse [8].…”
Section: Introductionmentioning
confidence: 99%